Teacher Competence from The Perspective of Imam Al-ghazali in The Book "Ayyuhal Walad" - Fatkhurrokhim, Fatkhurrokhim; Betty Mauli Rosa Bustam (SALIHA: Jurnal Pendidikan Islam, 2024)
Kompetensi Guru Perspektif Imam Al-ghazali Dalam Kitab “Ayyuhal Walad”. This study highlights the critical issue of the lack of teacher competence, which hinders the achievement of educational goals. According to the 2016 Global Education Monitoring report by UNESCO, the quality of teachers in Indonesia ranks the lowest among 14 developing countries analyzed. The study aims to identify aspects of teacher competence in the book “Ayyuhal Walad” by Al-Ghazali and relate them to the modern educational context. The approach used is qualitative library research with content analysis techniques. Data were analyzed to identify the main aspects of teacher competence according to Al-Ghazali. The results show that Al-Ghazali emphasizes the importance of knowledge as the primary requirement to become a teacher, accompanied by three additional conditions: avoiding love for worldly things and positions, having a quality mentor, and practicing self- discipline through riyadhah (spiritual exercises). This research demonstrates the alignment between Al-Ghazali’s views on teacher competence and the teacher competence outlined in Law Number 14 of 2005 on Teachers and Lecturers. This conclusion is beneficial for developing educational quality by integrating classical and modern values in forming teacher competence